Factores asociados al consumo de frutas y verduras en clientes de comedores populares de Lima, Perú - Díaz Garcés, Flavia Alesandra (2016)
Introduction Community Kitchens (CKs) are one of the main providers of food to low-income families in Peru and may serve to improve the offer of healthier diets. This study aims to determine the prevalence of, and sociodemographic and behavioral factors associated with fruits and vegetables consumption among CKs customers. Methods A cross-sectional study enrolling customers of 48 CKs in two areas of Lima, Peru, was performed. The outcome variable was the self-reported amount of fruits and vegetables consumed (<5 vs. ≥5 servings/day). The exposures were grouped in sociodemographic variables (age, gender, education level, familial income, marital status, and place of birth), and self- reported intention to change eating and exercise related habits in the last four weeks before interview. Poisson regression models were used to estimate prevalence ratios (PR) and 95% confidence intervals (95% CI). Results Data from 422 persons were analyzed, 328 females (77.9%), mean age 43.7 (±14.5) years. Only 36 (8.5%; 95% CI 5.9%-11.2%) customers reported consuming ≥5 servings of fruits and vegetables per day. This pattern was 4-fold more likely among those with higher levels of education (≥12 vs. <7 years) and 64% less common for migrants born outside of Lima relative non-migrants. In terms of intentions to change eating-related habits, those who reported having tried to reduce sugar consumption or to eat more fruits were up to 90% more likely to meet the ≥5 servings/day target. Conclusions A substantial gap in the consumption of ≥5 servings of fruits and vegetables/day has been found among CK customers and apparently it is not dependent of familial income. The profiles reported in this study can inform appropriate strategies to increase healthier eating in this population.